2014
DOI: 10.1111/pbi.12274
|View full text |Cite
|
Sign up to set email alerts
|

A combination of gene expression ranking and co‐expression network analysis increases discovery rate in large‐scale mutant screens for novel Arabidopsis thaliana abiotic stress genes

Abstract: SummaryAs challenges to food security increase, the demand for lead genes for improving crop production is growing. However, genetic screens of plant mutants typically yield very low frequencies of desired phenotypes. Here, we present a powerful computational approach for selecting candidate genes for screening insertion mutants. We combined ranking of Arabidopsis thaliana regulatory genes according to their expression in response to multiple abiotic stresses (Multiple Stress [MST] score), with stress-responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 65 publications
(93 reference statements)
0
14
1
Order By: Relevance
“…This is an important finding since it shows that the scale and scope of gene activity is not simply the molecular function of a gene, but a consequence of its spatial location, timing of expression, and responsiveness to environmental conditions. It also helps to provide an explanation for the typically higher hit rate in identifying phenotypes in regulators identified in systems biology data set analysis using a reverse genetic approach (Ransbotyn et al, 2015); a higher level specificity in the measurement of expression levels, regulation, and location of genes means that investigators can determine more precise and accurate predictions of when perturbation of function might lead to a measurable phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important finding since it shows that the scale and scope of gene activity is not simply the molecular function of a gene, but a consequence of its spatial location, timing of expression, and responsiveness to environmental conditions. It also helps to provide an explanation for the typically higher hit rate in identifying phenotypes in regulators identified in systems biology data set analysis using a reverse genetic approach (Ransbotyn et al, 2015); a higher level specificity in the measurement of expression levels, regulation, and location of genes means that investigators can determine more precise and accurate predictions of when perturbation of function might lead to a measurable phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Microarray resource databases including ATTED‐II (Obayashi et al ., ; Aoki et al ., ), Genevestigator (Zimmermann et al ., , ), AtGenExpress (Kilian et al ., ; Goda et al ., ), OryzaExpress (Hamada et al ., ), BAR (Patel et al ., ), At‐TAX (Laubinger et al ., ), PRIMe (Akiyama et al ., ), CORNET (De Bodt et al ., , ), PathoPlant (Bulow et al ., ), PLEXdb (Dash et al ., ) and ePlant (Fucile et al ., ) are few of many databases developed to perform co‐expression analysis using thousands of microarray datasets from Arabidopsis and other model plants. These microarray resources have contributed to the functional characterization of numerous genes in Arabidopsis and other plants (Mao et al ., ; Yonekura‐Sakakibara and Saito, ; Amrine et al ., ; Costa et al ., ; Ransbotyn et al ., ).…”
Section: Omics Toolsets and Analysis To Discover Unknownsmentioning
confidence: 97%
“…Nevertheless, it is abstract enough to be applied to all kinds of biological data. It has been demonstrated that co-expression networks are able to effectively identify pathways and candidate biomarkers [6] or reveal gene modules representing a biological process perturbed in a disease [7], just to name a few examples, and the similarity-based approach remains the dominant method of functional network inference today, with many recent examples: [812]. …”
Section: Introductionmentioning
confidence: 99%